2014
DOI: 10.1007/s13277-014-2800-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of OLIG2 as the most specific glioblastoma stem cell marker starting from comparative analysis of data from similar DNA chip microarray platforms

Abstract: Despite advances in surgical and adjuvant treatments, overall survival of glioblastoma (GBM) patients remains poor. The cancer stem cell concept suggests that a rare stem cell population, called glioma stem cells (GSCs), has high ability to self-renewal leading to recurrence in GBM. The identification of specific markers of GSCs would provide a powerful tool to detect and to characterise them in order to develop targeted therapies. We carried out a comparative analysis based on the identification of inter-stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 95 publications
3
37
1
Order By: Relevance
“…Our results reveal that this gene is also a potential tumor suppressor in glioblastomas as it is significantly downregulated in glioblastoma samples. In the current study TUSC3 is inversely correlated with Olig2 expression in patient samples, which is a specific GBM cancer stem cell marker (Trepant et al, 2015). Nevertheless, TUSC3 had a positive correlation with tumor size, which is a contradictory result.…”
Section: Discussioncontrasting
confidence: 61%
“…Our results reveal that this gene is also a potential tumor suppressor in glioblastomas as it is significantly downregulated in glioblastoma samples. In the current study TUSC3 is inversely correlated with Olig2 expression in patient samples, which is a specific GBM cancer stem cell marker (Trepant et al, 2015). Nevertheless, TUSC3 had a positive correlation with tumor size, which is a contradictory result.…”
Section: Discussioncontrasting
confidence: 61%
“…Cyclin D2 is rarely expressed in normal brain or low grade glioma and is significantly upregulated in GBM . Regarding GSCs, we have previously shown that CCND2 is part of the most differentially expressed genes between differentiated and GSC enriched cultures from similar DNA chip microarray platforms . In the same way, Koyama‐Nasu et al demonstrated by immunoblotting analysis and RT‐PCR that Ccnd2 is abundantly expressed only in undifferentiated GBM cell lines, which was not the case for Cyclin D1 and D3.…”
Section: Discussionmentioning
confidence: 69%
“…This same paradigm has also been seen in brain tumors. For example, the bHLH transcription factor OLIG2 is required for self-renewal of normal neural progenitor cells (Imayoshi and Kageyama, 2014) and is also a marker of glioblastoma TPCs (Beyeler et al, 2014; Ligon et al, 2007; Suvà et al, 2014; Trépant et al, 2015). Our results in RMS parallel those outlined for T-ALL and glioblastoma, showing that MRFs are capable of reprogramming differentiated RMS cells into TPCs and are required for sustained proliferation and viability of human RMS.…”
Section: Discussionmentioning
confidence: 99%